2006
DOI: 10.1007/s00239-005-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

The ATL Gene Family from Arabidopsis thaliana and Oryza sativa Comprises a Large Number of Putative Ubiquitin Ligases of the RING-H2 Type

Abstract: Ubiquitin ligases play an important regulatory role in the control of protein degradation processes via the ubiquitin/26S proteasome pathway in eukaryotes. These enzymes participate in substrate specification and mediate the transfer of ubiquitin to target proteins. A large number of ubiquitin ligases are predicted in the eukaryotes whose genomes have been sequenced; in Arabidopsis thaliana more than 1300 genes are thought to encode ubiquitin ligases. At least three classes of ubiquitin ligases are present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(157 citation statements)
references
References 36 publications
7
150
0
Order By: Relevance
“…The C-terminal region of ATL proteins is predicted to recognize specific target proteins for ubiquitination because the region is not conserved among the ATL family, unlike the N-terminal hydrophobic region and RING domain (11). According to this hypothesis, our study demonstrates that the interaction of ATL31 with 14-3-3 proteins is mediated by the phosphorylation of specific Ser/Thr residues in the C-terminal region.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The C-terminal region of ATL proteins is predicted to recognize specific target proteins for ubiquitination because the region is not conserved among the ATL family, unlike the N-terminal hydrophobic region and RING domain (11). According to this hypothesis, our study demonstrates that the interaction of ATL31 with 14-3-3 proteins is mediated by the phosphorylation of specific Ser/Thr residues in the C-terminal region.…”
Section: Discussionmentioning
confidence: 80%
“…ATL31 overexpression led to a carbon/nitrogen-insensitive phenotype of carbon/nitrogen insensitive 1-dominant (cni1-D) plants and resulted in expansion of green-colored cotyledon under high carbon/low nitrogen conditions, whereas the loss-of-function mutant of ATL31 showed a hypersensitive phenotype (9). ATL31 is a member of the plant-specific ATL ubiquitin ligase family, which comprises proteins that contain a transmembrane-like hydrophobic region at the N terminus, a GLD region, a RING-H2 type zinc finger domain, and a nonconserved C-terminal region (11). Biochemical and genetic studies demonstrated the membrane localization and ubiquitin ligase activity of ATL31, both of which are required for the regulation of C/N-nutrient response in plants (9).…”
mentioning
confidence: 99%
“…KEG has been implicated in the regulation of ABI5 protein levels in the absence of stress (Stone et al, 2006). ATL43 has been proposed to function as a positive regulator of ABA responses because atl43 mutant T-DNA lines were moderately insensitive at high concentration of ABA during germination (Serrano et al, 2006). Increased expression of XERICO was found to increase endogenous ABA levels and XERICO was thought to regulate the expression of an ABA biosynthesis gene (Ko et al, 2006).…”
Section: Atpub Proteins and S-domainmentioning
confidence: 99%
“…RING-finger proteins are a group of E3 ligases that mediate the transfer of ubiquitin to proteins and target substrates to the proteasome, an important part of the protein degradation system, via the ubiquitin/26S proteasome pathway (Glickman and Ciechanover 2002). Ubiquitinmediated proteasome pathways have been suggested to play an important role in the early stages of plant embryogenesis (Shen et al 2002, Hellmann et al 2003, Liu et al 2004, and Arabidopsis mutants of RING-finger type E3 ligase show seed deficiency (Serrano et al 2006). Based on these observations, E-14-2 was expected to be an embryospecific gene with an important role in early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%